2011
DOI: 10.1002/pbc.23117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychiatric diagnoses on hospital length of stay in children with sickle cell anemia

Abstract: Pediatric patients diagnosed with a psychiatric disorder, specifically mood or anxiety disorders, have longer LOS for VOC. These findings suggest that future interventions aimed at managing VOC may need to consider adjunctive psychiatric assessment and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…children with sickle cell anemia). 10;11 We performed a serial cross-sectional analysis of KID hospitalizations in 2003, 2006, and 2009.…”
Section: Methodsmentioning
confidence: 99%
“…children with sickle cell anemia). 10;11 We performed a serial cross-sectional analysis of KID hospitalizations in 2003, 2006, and 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in adult patients with SCD have found associations between mental health symptoms and healthcare utilization (i.e., emergency department utilization, hospital admissions) 5–7. Within the pediatric population, our prior work in SCD found that admissions for SCD pain management were longer when a mental health diagnosis, specifically a mood, anxiety, or substance use disorder, was present upon discharge highlighting the impact of mental health on an individual's ability to cope with pain within the hospital 8. However, mental health disorders also have the potential to impact an individual's ability to manage pain at home resulting in increased admissions for pain.…”
Section: Introductionmentioning
confidence: 97%
“…410 Among children with complex chronic illnesses, comorbid mood and anxiety disorders are associated with more inpatient utilization; e.g. more admissions, 11,12 longer admissions, 13 and more re-hospitalizations. 14 …”
Section: Introductionmentioning
confidence: 99%